Immunohistochemical characterization of non‐epithelial cells in spiradenoma. Issue 11 (23rd September 2013) - Iida, Kohji; Iwai, Shinsaku; Hosaka, Hiroomi; Kitami, Yuki; Akiyama, Masaki; Suzuki, Takao; Sueki, Hirohiko
Abstract: Spiradenoma is unique with respect to the presence of a large number of non‐epithelial cells, including S100 protein + cells, most of which are presumably Langerhans cells, in the parenchyma as shown in the published work. However, the characterization of these non‐epithelial cells to date is insufficient. Immunohistochemistry of CD1a, CD3, CD4, CD8, CD56, CD68, intercellular adhesion molecule‐1 (ICAM‐1), and HLA‐DR, as well as double‐immunofluorescence labeling of S100 protein/CD1a and CD1a/CD3, was performed using paraffin‐embedded specimens from five cases of spiradenoma retrospectively. Non‐epithelial cells evenly distributed throughout the parenchyma of spiradenoma primarily consisted of CD1a + Langerhans cells and CD3 + T cells. ICAM‐1 was expressed by epithelial cells and non‐epithelial cells in the parenchyma. HLA‐DR on the epithelial cells was limited to the focal area. In double‐immunofluorescence labeling, approximately one‐half of Langerhans cells were spatially related to T cells in the parenchyma, suggesting their functional interaction.